AN IMPROVEMENT TO ADJUSTABLE TABLE DESIGN: Indonesia - Rengkung, Jeremy; Cardiah, Tita (Universitas Telkom, 2021)
Improved design adjustable desk is related to a table that can be adjusted in position. This table can be used not only in a forward and backward tilted position, but can also be used in left and right side tilted position, so there will be more activities that can be adjusted to the needs and desires of the user. The purpose of this study is to develop a design by providing innovation to the adjustable desk that is already on the market so that the table is more multifunctional when used by users. This study uses an adjustable desk design development method, through data collection from observations, interviews, questionnaires, literature studies, data analysis, and design results. Based on the results of the discussion, it was found that the adjustable desk will add several buffer components to the table for one person with the table surface that can be adjusted according to the user's wishes, in 30o, 45o, 60o, and 90o tilted positions. The tilt position of the table is regulated by a tilt lock to make it easier for users to adjust the position of the table surface by moving the table surface to the desired position. The results of this design development will be a guide for industrial design. Keywords: Improved design, adjustable desk, Multifunction Furniture